(untitled) (Atti del Sodalizio Glottologico Milanese, 2019)
Starting from Kastovsky’s definition of “morphological syntagm”, I try to understand whether any similarity exists between complex word forms (such as compounds and secondary derivatives) and the matching source-phrases which should be taken into account in the relevant formation-rules according to Pāṇini’s teaching. Thus, A 2.1.1 is interpreted and tested in a fresh manner, leading to the outline of a a scalar pattern of iconicity which encompasses the several outputs of the provisions it governs. KEYWORDS: morhpological syntagms, iconicity, Pāṇini, Sanskrit, word formation